Balancing Wellness and Learning: Self-Care Practices for Educators - Akhtarullah, Shazia; Niazi, Fariha (Experiential Learning and Teaching in Higher Education, 2026)
Experiential education often requires educators to be deeply involved in the learning process with enhanced preparation, coordination, and logistical work, which may require significant time and effort. Faculty and staff development that includes self-care strategies to enhance their overall well-being is thus becoming crucial for experiential educators. By prioritizing self-care, educators can better navigate the demands of experiential education and maintain their well-being, ultimately benefiting themselves, their students, and their communities of interest. In this paper, readers will review self-care as a multifaceted phenomenon, explore self-care strategies, and learn to integrate them into their daily routines to build resilience. Keywords: experiential education, faculty development, self-care, self-care strategies